Avian influenza virus ecology and evolution through a climatic lens. (October 2018) - Morin, Cory W.; Stoner-Duncan, Benjamin; Winker, Kevin; Scotch, Matthew; Hess, Jeremy J.; Meschke, John S.; Ebi, Kristie L.; Rabinowitz, Peter M.
Abstract: Avian influenza virus (AIV) is a major health threat to both avian and human populations. The ecology of the virus is driven by numerous factors, including climate and avian migration patterns, yet relatively little is known about these drivers. Long-distance transport of the virus is tied to inter- and intra-continental bird migration, while enhanced viral reassortment is linked to breeding habitats in Beringia shared by migrant species from North America and Asia. Furthermore, water temperature, pH, salinity, and co-existing biota all impact the viability and persistence of the virus in the environment. Changes in climate can potentially alter the ecology of AIV through multiple pathways. Warming temperatures can change the timing and patterns of bird migration, creating novel assemblages of species and new opportunities for viral transport and reassortment. Water temperature and chemistry may also be altered, resulting in changes in virus survival. In this review, we explain how these shifts have the potential to increase viral persistence, pathogenicity, and transmissibility and amplify the threat of pandemic disease in animal and human hosts. Better understanding of climatic influences on viral ecology is essential to developing strategies to limit adverse health effects in humans and animals. Highlights: East Asia and Beringia are regional focal points for AVI ecology. Agriculture, poultry, climate, and bird migration all influence AIV ecology. Climate change may impact the dynamics of AIV evolution and transmission. Climate driven changes in bird migration patterns may impact global AIV transport. Changing agricultural practices may impact transmission of AIV between birds.